Resistance thermometers based on the germanium films - Mitin, V.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The latest achievements in the field of development of resistance thermometers based on the germanium films on gallium arsenide are presented and summarized. Basic models of Ge film thermometers, which cover the temperature range from 0.02 to 500 K, are considered. Characteristics of the thermometers in high magnetic fields and under the action of ionizing irradiation (neutrons and gamma-rays) are presented.